Increased Abundance of Nuclear HDAC4 Impairs Neuronal Development and Long-Term Memory - Main, Patrick; Tan, Wei Jun; Wheeler, David; Fitzsimons, Helen L. (Frontiers in Molecular Neuroscience, 2021)
Dysregulation of the histone deacetylase HDAC4 is associated with both neurodevelopmental and neurodegenerative disorders, and a feature common to many of these disorders is impaired cognitive function. HDAC4 shuttles between the nucleus and cytoplasm in both vertebrates and invertebrates and alterations in the amounts of nuclear and/or cytoplasmic HDAC4 have been implicated in these diseases. In Drosophila, HDAC4 also plays a critical role in the regulation of memory however the mechanisms through which it acts are unknown. Nuclear and cytoplasmically-restricted HDAC4 mutants were expressed in the Drosophila brain to investigate a mechanistic link between HDAC4 subcellular distribution, transcriptional changes and neuronal dysfunction. Deficits in mushroom body morphogenesis, eye development and long-term memory correlated with increased abundance of nuclear HDAC4 but were associated with minimal transcriptional changes. Although HDAC4 sequesters MEF2 into punctate foci within neuronal nuclei, no alteration in MEF2 activity was observed on overexpression of HDAC4, and knockdown of MEF2 had no impact on long-term memory, indicating that HDAC4 is likely not acting through MEF2. In support of this, mutation of the MEF2 binding site within HDAC4 also had no impact on nuclear HDAC4-induced impairments in long-term memory or eye development. In contrast, the defects in mushroom body morphogenesis were ameliorated by mutation of the MEF2 binding site, as well as by co-expression of MEF2 RNAi, thus nuclear HDAC4 acts through MEF2 to disrupt mushroom body development. These data provide insight into the mechanisms through which dysregulation of HDAC4 subcellular distribution impairs neurological function and provides new avenues for further investigation.